Energy Storage: Giant Enhancement in the Supercapacitance of NiFe–Graphene Nanocomposites Induced by a Magnetic Field (Adv. Mater. 28/2019). Issue 28 (10th July 2019) - Romero, Jorge; Prima‐Garcia, Helena; Varela, Maria; Miralles, Sara G.; Oestreicher, Víctor; Abellán, Gonzalo; Coronado, Eugenio
Abstract : The application of external magnetic fields to NiFe–graphene nanocomposites during the galvanostatic charge/discharge cycles induces a dramatic metal phase segregation, forming nanometric metal clusters of Ni with an outstanding electrochemical activity. This metal segregation leads to an enhancement in the capacitance of the nanocomposite, as described by Gonzalo Abellán, Eugenio Coronado, and co‐workers in article number1900189 .